2020
DOI: 10.7759/cureus.9413
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sickle Cell Disease and Sudden Onset Sensorineural Deafness

Abstract: Sickle cell anemia (SCA) is a hereditary hemoglobin (Hb) disorder associated with a very specific molecular lesion, which is the exchange of glutamic acid for valine in the sixth residue of the Hb beta chain, originating the S Hb. It is characterized by intermittent episodes of vascular occlusion and end-organ damage. Progressive organ damage may affect any organ with brain, eyes, pulmonary, hepatobiliary, spleen, genitourinary, and the musculoskeletal systems being the most commonly involved and reported. Oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…14 Studies have documented that the younger age is at a higher risk of developing hearing loss because the microvasculature of the cochlea in young infants may be more susceptible to damage during a sickle cell crisis. 9,10 Our study found hearing loss in the older age group, in contrast to the higher risk of developing SNHL in children with SCD. 18 The average hearing threshold of patients with SCD in this study falls within the normal range but was consistently higher than that of the controls, similar to findings from other studies.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…14 Studies have documented that the younger age is at a higher risk of developing hearing loss because the microvasculature of the cochlea in young infants may be more susceptible to damage during a sickle cell crisis. 9,10 Our study found hearing loss in the older age group, in contrast to the higher risk of developing SNHL in children with SCD. 18 The average hearing threshold of patients with SCD in this study falls within the normal range but was consistently higher than that of the controls, similar to findings from other studies.…”
Section: Discussionmentioning
confidence: 43%
“…Much need to be known about the relationship between SCD and hearing impairment. 9,10 Histopathological degenerative changes in the cochlear are consistent with ischaemic injuries observed in SCD. 11 Several studies have documented the varying prevalence of hearing loss in patients with SCD ranging from 0.2%-66%.…”
Section: Introductionmentioning
confidence: 58%
“…Acute complications include acute chest syndrome (ACS), vaso‐occlusive crisis (VOC), hepatobiliary complications, stroke, splenic sequestration, priapism, acute anemia, and fever 8 . Chronic complications are pulmonary hypertension, hepatic iron overload, kidney disease, avascular necrosis, retinopathy, and legs ulcer 7,9‐12 . Among the acute complications, the most common are VOC and ACS.…”
Section: Discussionmentioning
confidence: 99%
“…8 Chronic complications are pulmonary hypertension, hepatic iron overload, kidney disease, avascular necrosis, retinopathy, and legs ulcer. 7,[9][10][11][12] Among the acute complications, the most common are VOC and ACS. VOCs are episodes of severe pain due to microvascular occlusion with erythrocytes and leukocytes, thus preventing blood flow and causing organ ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Acute complications include: Acute chest syndrome (ACS), Vaso-occlusive crisis (VOC), hepatobiliary complications, stroke, splenic sequestration, priapism, acute anemia, and fever [8]. Chronic complications are pulmonary hypertension, hepatic iron overload, kidney disease, avascular necrosis, retinopathy, and legs ulcer [7,[9][10][11][12]. Among the acute complications, the most common are VOC and ACS.…”
Section: Discussionmentioning
confidence: 99%